Understanding ICD-10-CM and ICD-10-PCS, 5th Edition - Mary Jo Bowie (Cengage Learning, 2020)
Master the latest 2020 ICD-10-CM and ICD-10-PCS coding guidelines and new 2020 ICD-10 codes with Bowie's UNDERSTANDING ICD-10-CM AND ICD-10-PCS: A WORKTEXT, 2020 EDITION. This unique, hands-on worktext is updated every year to provide the latest comprehensive coverage of today's ICD-10-CM and ICD-10-PCS diagnostic and procedural coding system. This edition's detail, yet easy-to-follow approach is packed with proven learning features and helpful tools to reinforce understanding. You immediately apply what you've learned with numerous professionally focused exercises, actual coding assignments and real case studies. Vivid color illustrations and the latest digital links to medical research websites demonstrate how a thorough knowledge of anatomy and disease processes can increase coding accuracy. Use this trusted resource to prepare for various certification exams as well as diagnostic and procedural coding success in today's medical environment.